The Development of Hemochromatosis after Treatment for Celiac Sprue - Mang Ma; Edmond A Ryan; Vincent G Bain (Canadian Journal of Gastroenterology)
Celiac sprue is a chronic disease characterized by maldigestion and malabsorption. Whereas many diseases have been reported in association with celiac sprue, hemochromatosis has not. A 62-year-old man with celiac sprue and a history of iron deficiency and osteopenic bone disease who developed hemochromatosis is reported. Liver biopsy showed portal tract fibrosis, early nodule formation and increased hepatic iron storage. The patient developed hemochromatosis with hepatic injury two years after his transferrin saturation became elevated and 10 years after he had been placed on gluten-free diet. Lifelong iron accumulation was prevented by chronic malabsorption of iron but hemochromatosis became manifest when his celiac sprue was treated.